Age‐related longitudinal change in cardiac structure and function in adults at increased cardiovascular risk. (7th April 2020) - Gong, Fei Fei; Coller, Jennifer M.; McGrady, Michele; Boffa, Umberto; Shiel, Louise; Liew, Danny; Stewart, Simon; Owen, Alice J.; Krum, Henry; Reid, Christopher M.; Prior, David L.; Campbell, Duncan J.
Abstract: Aim: Heart failure (HF) incidence increases markedly with age. We examined age‐associated longitudinal change in cardiac structure and function, and their prediction by age and cardiovascular disease (CVD) risk factors, in a community‐based cohort aged ≥60 years at increased CVD risk but without HF. Methods and results: CVD risk factors were recorded in 3065 participants who underwent a baseline echocardiographic examination, of whom 2358 attended a follow‐up examination 3.8 [median, inter‐quartile range (IQR) 3.5, 4.2] years later. Median age was 71 (IQR 67, 76) years and 55% of participants were male. Age was associated with longitudinal increase in left ventricular (LV) mass index (LVMI); decrease in LV volumes; increase in LV ejection fraction; decrease in mitral annular systolic velocity; decrease in diastolic function (decreased mitral early diastolic annular velocity (e′); and increase in left atrial volume index, mitral peak early diastolic flow velocity (E)/e′ ratio, and tricuspid regurgitant velocity (TRVmax ) in men and women, except for TRVmax in men). In multivariable analysis, longitudinal increase in LVMI was explained by CVD risk factors alone, whereas age, together with CVD risk factors, independently predicted longitudinal change in all other echocardiographic parameters. CVD risk factors were differentially associated with longitudinal change in different echocardiographic parameters. Conclusions: Whereas the increase in LVMI with age was explained by CVD risk factors alone, age, together with risk factors, independently predicted longitudinal change in all other echocardiographic parameters, providing evidence for age‐specific mechanisms of change in cardiac structure and function as people age. Age‐associated change in LVMI, LV volumes, and diastolic function resembled what might be expected for the evolution of HF with preserved ejection fraction. Given the differential association of different CVD risk factors with longitudinal change in different echocardiographic parameters, therapies aimed at attenuation of age‐associated change in cardiac structure and function, and HF evolution, will likely need to address multiple CVD risk factors.